Renovation of Crane Control System of Reach Stalker Ferari 178h1 Using Avr Atmega2560 - Markis, Lince; Wardana, P.Susetyo; Syawaldipa, Ardi (SOTVI, 2022)
Container rental service companies or container parking facilities providers need container transportation equipment such as Crane Reach Stalker to move and arrange containers. Several container services companies in Surabaya such as Citra Mandiri Sejati have a Crane Reach Stalker made by Ferari Italy which experienced damage to the electrical control. After observing the control unit, the damage was in the hardware comparison system and the relay control used. Dealing with these problems, planning and improvement of the total control system were carried out using the ATMega2560 AVR microcontroller. However, the problem becomes complex and requires cooperation with Hydraulic control partners when the entire system must be resolved. From the renovation work on the Ferari 178H1 Load Handling Crane system for a year, it was obtained that the Load Handling control input data in which it was a joystick and a 3 positions button with an output level of 0 and 9 volts. Hydraulic control uses a Solenoid Valve type 4/3 with 2 input control coils, and in overall system testing, the average length of time for the movement of the Piston Crane is 6 to 12 seconds. From the test results using a 40 tons container load, it was stated by the Crane driver that the time used to carry out Load Handling for the Hydraulic type and the Crane's age was suitable and appropriate. Â